Multicolor photoreactions of the red light–activated channelrhodopsin Chrimson - Johannes Vierock; Joel C. D. Kaufmann; Lukas Faiß; Linda Tillert; Benjamin S. Krause; Paul Fischer; Thi Bich Thao Nguyen; Dietmar Schmitz; Benjamin R. Rost; Franz Bartl; Peter Hegemann (Proceedings of the National Academy of Sciences, 2025)
Channelrhodopsins are light-gated ion channels that are used in modern neurosciences for the precise control of cellular ion fluxes by light. With a peak absorption at 585 nm, Chrimson is the most red-shifted cation-conducting ChR. It is frequently employed in multicolor experiments alongside blue light–sensitive optogenetic tools and is so far the only light-gated ion channel successfully applied in human vision restoration. However, its photoresponses to different wavelengths have not been thoroughly characterized. In this study, we identify multiple interconvertible dark states of Chrimson with distinct absorption and photokinetic properties. Combining electrophysiology and spectroscopy with optogenetic experiments in neurons, we unveil that this dark state heterogeneity is based on distinct protonation dynamics of the counterion complex and alternative retinal isomerization. In neurons, prolonged red illumination reduces Chrimson’s red light sensitivity, which is reflected by a blue shift of the action spectrum. Blue light pulses reverse this shift and increase the excitability in subsequent red-light flashes. This understanding of wavelength-dependent photoreactions in Chrimson will improve the design of multicolor optogenetic experiments and inform strategies for optimizing Chrimson for therapeutic applications.